1998
DOI: 10.1200/jco.1998.16.10.3380
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of improved outcome for patients with localized prostate cancer treated with neoadjuvant androgen ablation therapy and three-dimensional conformal radiotherapy.

Abstract: For patients treated with NAAD and high-dose 3D-CRT, pretreatment PSA, preradiotherapy PSA nadir response, and clinical stage are important predictors of biochemical outcome. Patients with NAAD-induced PSA nadir levels greater than 0.5 ng/mL before radiotherapy are more likely to develop biochemical failure and may benefit from more aggressive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 15 publications
1
45
1
Order By: Relevance
“…While the pre-radiotherapy PSA correlates significantly with outcome in terms of freedom from PSA failure on univariate analysis (Table 2), it also correlates with presenting PSA, and is no longer statistically significant on multivariate analysis. The discrepancy between our findings and those of Zelefsky et al (1998) could reflect differences in the study populations, or the relative insensitivity of the PSA assay used in the early part of our series.…”
Section: Clinicalcontrasting
confidence: 93%
See 2 more Smart Citations
“…While the pre-radiotherapy PSA correlates significantly with outcome in terms of freedom from PSA failure on univariate analysis (Table 2), it also correlates with presenting PSA, and is no longer statistically significant on multivariate analysis. The discrepancy between our findings and those of Zelefsky et al (1998) could reflect differences in the study populations, or the relative insensitivity of the PSA assay used in the early part of our series.…”
Section: Clinicalcontrasting
confidence: 93%
“…This is somewhat analagous to the clinical findings of Zelefsky et al (1998), who in their study of 213 men with clinically localised prostate cancer, found that a pre-radiation PSA of 50.5 ng ml 71 following neoadjuvant androgen deprivation was an independent favourable prognostic factor. We attempted to address this issue by testing the PSA measured immediately pre-radiotherapy as a possible predictive factor for biochemical control.…”
Section: Clinicalmentioning
confidence: 59%
See 1 more Smart Citation
“…13 While this study was not designed to evaluate the effect of neoadjuvant hormonal therapy, 29% of patients had received this treatment to produce downsizing, with up to 81 Gy of radiation delivered to the bladder, rectum, seminal vesicles and prostate. This study demonstrated that 4 y survival depended on the number of favourable classical prognostic factors, including PSA, staging and Gleason score (Table 5), while the response was found to be better if 75.6 Gy or above was used.…”
Section: Review Of the Literature: Radiation With Or Without Neoadjuvmentioning
confidence: 99%
“…52 ,.1, 6 2 One refinement, for example, is the toticbiomarkers, changes in degree or new occurrence of concept that any changes in SEB must actually meet the PIN, cell/nuclear morphometry, chromosomal changes, requirement of "predicting" the likelihood of the actual and QOL parameters. Any modulations noted in SEB endpoint rather than merely "correlating with" it.…”
mentioning
confidence: 99%